The YouTube Media Utilization in Islamic Religious Education Learning - Sahdiana Rahmadani; Faisal Amir Toedien; Kalayo Hasibuan (SEULANGA SYSTEM PUBLISHER, 2024)
Using YouTube in Islamic Religious Education (PAI) has become a powerful alternative to support and enrich the teaching and learning experience in the digital era. YouTube offers a wide range of educational content that can be accessed effortlessly, anytime, anywhere. With video format, Islamic learning materials such as Al-Qur’an, Hadith, Islamic history, and fiqh can be delivered more interactively and interestingly, thus increasing students’ understanding. This research examines the use of YouTube as a learning media in Islamic Education and the benefits and challenges faced in its implementation. The results show that YouTube can enrich learning experiences, increase student motivation, and facilitate understanding religious concepts more dynamically and enjoyably. However, challenges such as varying content quality, lack of control over material not by Islamic teachings, and limited technological skills among some educators are still obstacles. Therefore, appropriate content selection and management strategies are needed to ensure the maximum utilization of YouTube in PAI learning.